2005
DOI: 10.1037/0022-006x.73.4.599
|View full text |Cite
|
Sign up to set email alerts
|

What Do Clinicians Expect? Comparing Envisioned and Reported Violence for Male and Female Patients.

Abstract: Mental health professionals' (MHPs') accuracy in assessing the risk of violence in female patients is particularly limited. Based on assessments made by 205 MHPs of 605 patients in an emergency room, this study explored potential causes of MHPs' poorer accuracy in assessing women's potential for violence. The dimensions that underlie MHPs' envisioned violence in patients were identified and were compared with those that characterized patients' reported violence during a 6-month follow-up period. There were thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The predictive utility of both clinically feasible methods examined here can be compared with that of clinical judgment and of leading risk assessment tools examined in other studies. First, the predictive utility of selfperceptions and (to a lesser extent) of the brief tools compares favorably with the utility of unaided clinical judgment observed in other studies (AUC=.61) (39). If replicated, this suggests that adding either method would be preferable to the current practice of relying upon judgment alone.…”
Section: Promise Of Clinically Feasible Methodsmentioning
confidence: 63%
“…The predictive utility of both clinically feasible methods examined here can be compared with that of clinical judgment and of leading risk assessment tools examined in other studies. First, the predictive utility of selfperceptions and (to a lesser extent) of the brief tools compares favorably with the utility of unaided clinical judgment observed in other studies (AUC=.61) (39). If replicated, this suggests that adding either method would be preferable to the current practice of relying upon judgment alone.…”
Section: Promise Of Clinically Feasible Methodsmentioning
confidence: 63%
“…For example, based on a sample of 116 youthful offenders (mean age = 16) followed for an average of 7 years, Stockdale et al (2010) found that the PCL:YV predicted general recidivism prior to age 18 quite well (area under the receiver operating characteristic curve, or AUC = .79)—at levels often observed with purpose-designed risk-assessment tools. But it predicted general recidivism during adulthood (after age 18) quite poorly (AUC = .63)—that is, at levels no better than those reported for unaided clinical judgment (Skeem et al, 2005). The fact that so-called psychopathic youth may not reliably continue criminal behavior into adulthood has both theoretical and applied implications: It both (a) suggests that making psychopathy part of the diagnostic criteria for conduct disorder may not improve our ability to identify a group of homogeneous children and adolescents who are likely to mature into antisocial adults (see “Efforts to Parse Conduct Disorder” above) and (b) contradicts assumptions that underpin dominant legal uses of juvenile-psychopathy measures, including whether to transfer youth to the adult criminal justice system (Viljoen et al, 2010).…”
Section: Research Reviewmentioning
confidence: 79%
“…If the same pattern is found with scales such as the PPI-R, it may suggest that it is not simply criminal behavior embedded in the PCL-R that drives the superior performance of the antisocial factor, but disinhibitory psychopathology more generally. Indeed, this possibility has some empirical support: Even after controlling for past criminal behavior, the PCL measures’ antisocial factor still predicts violence (e.g., Skeem & Mulvey, 2001), suggesting that it assesses traits of antagonism and/or disinhibition that are not necessarily psychopathic but raise one’s likelihood of involvement in violence (see Skeem et al, 2005).…”
Section: Research Reviewmentioning
confidence: 99%
“…Treatment recommendations are conditioned on diagnostic impressions. Violence risk assessments are conditioned on predictions of future behavior 14 . Frequently, interventions are conditioned on meeting a threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Violence risk assessments are conditioned on predictions of future behavior. 14 Frequently, interventions are conditioned on meeting a threshold. For instance, the Veterans Administration's ''pain as the 5th vital sign'' initiative calls for a comprehensive assessment if the patient's numeric rating scale pain score is at least 4 15 ; rheumatology guidelines recommend a treatment change if disease activity meets a severity criterion.…”
Section: Introductionmentioning
confidence: 99%